Penelitian Perancangan Bisnis Pawty! Party Planner - Chatrine Putri; Marina Wardaya (Universitas Ciputra Surabaya, 2016)
Along with the times in this modern era, quite a lot of animal lovers who wanted to hold an event that can involve their pets with the aim to having a unique moment or increasing the prestige. However, not many companies that can help to organize the event. This study aims to find the right solution to resolve the issue. The methods that used in this research is primary data collection methods through interviews, and secondary which collects data from the literature and the Internet. The result that obtained from this study is developing a party planner for pets.